THE PREVALENCE OF MUSCULOSKELETAL INJURIES AMONG TRIATHLETES: A SYSTEMATIC REVIEW WITH META-ANALYSIS (Functional Plant Breeding Journal, 2022)
The aim of this systematic review was to estimate the general prevalence of musculoskeletal injuries in triathletes. The study protocol was registered in PROSPERO (CRD42020210540). This systematic review with meta-analysis included cross-sectional and cohort studies that investigated a 12-month prevalence of musculoskeletal injuries, regardless of injury type. Studies that analyzed only one body area of ​​the triathlete were excluded. The databases searched were Embase, Medline, Scopus, SPORDiscus, Web of Science, Lilacs, SciELO and CINAHL. The methodological quality and level of certainty of the evidence were assessed using the JBI Critical Appraisal Tool and the GRADE approach, respectively. Prevalence analysis was performed using the random effect model. Begg-Mazumdar and Egger tests were applied to assess publication bias. Nine studies were included in this review, totaling 2096 participants (81,4% men). The overall prevalence of musculoskeletal injuries at 12 months was 54% (I2=98.5%, 95%CI 36–71%). The body region with the highest prevalence of injuries was the foot and ankle, with 27% (I2=92.7%, 95%CI 17-36%). The prevalence of musculoskeletal injury in women and men was similar. This systematic review provides important information for sports medicine specialists who make decisions about appropriate injury prevention measures.